2022
DOI: 10.16875/stem.2022.23.4.47
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Reading Aloud, Writing, and Assessment Through Voice Recording With EFL Learning

Abstract: This study attempts to develop an EFL learning output activity by integrating reading aloud, writing, and assessment through voice recording. 62 college students participated in the activities for 15 weeks. Surveys, self-evaluations, and teacher evaluations were conducted and analyzed using the SPSS t-test to examine the students’ reactions to the activities. The survey results for the psychological questionnaires on confidence, anxiety, and attitude toward English were not statistically significant except wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Notably, anxiety and confidence are recurring themes in studies exploring EFL learning. Anxiety, often described as a feeling of tension and unease related to the language learning process (Horwitz, Horwitz, & Cope, 1986), consistently emerges as a determinant in EFL learning outcomes (Chong, 2019(Chong, , 2021(Chong, , 2022Matsuda & Gobel, 2004;Tsang, 2022). Matsuda and Gobel (2004) explored the relationship between language anxiety and reading comprehension among EFL learners and found that anxiety negatively affected reading comprehension, and that learners with high anxiety tended to avoid reading in English.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, anxiety and confidence are recurring themes in studies exploring EFL learning. Anxiety, often described as a feeling of tension and unease related to the language learning process (Horwitz, Horwitz, & Cope, 1986), consistently emerges as a determinant in EFL learning outcomes (Chong, 2019(Chong, , 2021(Chong, , 2022Matsuda & Gobel, 2004;Tsang, 2022). Matsuda and Gobel (2004) explored the relationship between language anxiety and reading comprehension among EFL learners and found that anxiety negatively affected reading comprehension, and that learners with high anxiety tended to avoid reading in English.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, high confidence levels have consistently demonstrated a positive correlation with proficiency, particularly in speaking (Chong, 2019(Chong, , 2021(Chong, , 2022Yu, 2022). In the studies of Chong (2019Chong ( , 2021 reveal that reading aloud activities significantly enhance the selfconfidence of EFL learners in spoken English.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations